Characterization of a human X mouse T cell hybridoma and identification of a clone secreting and binding interleukin-2. - Durrant, L G (1984)
Human lymphocytes stimulated with phytohaemagglutinin (PHA) were fused with an HGPRT- murine lymphoma, BW5147, and a hybridoma BwFc93-1 was isolated and cloned in agarose. This human X mouse hybrid and nine clones derived from it were characterized by chromosome analysis, phenotypic and functional assays. Karyotyping and isoenzyme studies showed the presence of five human chromosomes in BwFc93-1 with preferential retention of three chromosomes--6, X and 15--in the clones. Membrane immunofluorescence analysis revealed that all the clones expressed human and mouse class 1 MHC antigens and the mouse T cell antigens Thy-1 and T200, but were devoid of human OKT3, OKT8 and mouse Lyt-2. Human OKT4 and OKM1 phenotypes were transiently expressed by one clone and mouse Lyt 1 by two other clones. Several T4-, Lyt-1- clones produced and bound human interleukin-2 (IL-2) indicating a lack of correlation between human T cell phenotype and function in those hybrids. There was also evidence of dichotomy in the secretion of IL-2 and expression of the IL-2 receptor since clones were identified which either bound or secreted IL-2. One clone expressing IL-2 receptors could be induced to produce human IL-2 by simultaneously stimulating with PHA and phorbol myristate acetate (PMA).